PROFESIONALISME KERJA PERANGKAT KELURAHAN DALAM PELAYANAN ADMINISTRASI PADA MASYARAKAT DI KANTOR KELURAHAN TALIKURAN BARAT KECAMATAN KAWANGKOAN UTARA - RUNKAT, REZA; DENGO, SALMIN; TAMPONGANGOY, DEYSI (JURNAL ADMINISTRASI PUBLIK, 2021)
In this study, the aim of this study was to find out how the professionalism of the village apparatus works in administrative services for the community at the West Talikuran Village Office, North Kawangkoan District. This study used descriptive qualitative method. The theory used in this study is the theory of indicators of work professionalism from Mertin Jr. which includes proficiency in using tools, readiness, responsibility in service, discipline and employee attitudes. The research informants were village officials and the community as recipients of administrative services, totaling 9 people. Data collection techniques that researchers use are observation, interviews, and documentation. Based on the findings of the research conducted, it can be concluded that the professionalism of the village apparatus in administrative services for the community at the West Talikuran Village Office, North Kawangkoan District can be said to be quite good even though it has not fully worked professionally because there are indicators that have not been carried out properly such as proficiency in using tools so that lack of employee skills in administrative services, lack of employees so that the organizational structure has not been filled, and employee discipline that must be improved again. So in conclusion, the professionalism of the village apparatus must be considered and improved in order to produce a better quality of administrative services. Keywords: Work Professionalism, Village Apparatus, Administrative Services.